Uniós polgárok és egyenlő bánásmód szociális jogok határai - Blutman László (Acta Universitatis Szegediensis : acta juridica et politica, 2007)
Union citizenship is the fundamental status of the nationals of Member States and free movement as laid down by Article 18(1) of the EC -Treaty is a fundamental right of Union citizens. European Court of Justice has in practice tended to interpret mobility rights generally in terms of EU citizenship, thus placing them into a single conceptual framework: Mobility rights may be connected to Article 12 of the EC Treaty on prohibition of discrimination on grounds of nationality. The paper examines the interplay between Articles 18(1) and 12 in some important cases in ECJ. It analyses the steps by which the ECJ extended social and other rights of the Union citizens availing themselves of the right to free movement of persons in ap plying these two provisions together.